Program Inkubator Usaha Tenun Pagatan sebagai Upaya Pembangunan Ekonomi Berbasis Komunitas Perempuan di Kabupaten Tanah Bumbu - Anjani Anjani; Muhammad Najeri Al Syahrin; Akhsanul Rahmatullah; Sri Hidayah; Charennina Marsha Diandra; Erin Erin; Fitri Annisa (BADAN PENERBIT STIEPARI PRESS, 2025)
The potential of rural women weavers in the Sabumi Group in Pagatan, Tanah Bumbu Regency, is highly significant, particularly in the villages of Manurung, Mundalang, and Saring. Among a total of 67 weavers, 63 are women, highlighting the dominant role of women in preserving and developing the traditional Pagatan weaving craft. This community service program aims to establish a Pagatan weaving business incubator through the formation of a youth group that functions as a center for training, production, and business development for women’s weaving communities. Additionally, the program seeks to create a digital platform for promoting and marketing Pagatan woven products through social media and online marketplaces. The implementation involved several stages, including mapping the complete network of weaving actors, conducting a SWOT analysis to identify strengths, weaknesses, opportunities, and threats, and providing training on digital marketing strategies. Furthermore, activities included content creation, product digitalization, and the establishment of a shared marketplace account to expand the market reach of woven products. One of the key achievements was the formation of the Kelompok Tenun Muda Majang Kaluku, consisting of 20 young weavers from Manurung and Mundalang villages. This group is expected to play a vital role in sustaining the weaving tradition while introducing modern business and marketing practices. Overall, this initiative demonstrates that integrating traditional skills with digital marketing innovation can enhance economic empowerment for rural women, foster cultural preservation, and strengthen local creative economies in Tanah Bumbu Regency.